PENGEMBANGAN INSTRUMEN TES DIAGNOSTIK THREE-TIER PADA PEMBELAJARAN SISTEM EKSKRESI BERDIFERENSIASI - Pretty Nurwhite Tika; Yunita Ainun Jariah; Maria Magdalena Melina; Rizhal Hendi Ristanto; Hanum Isfaeni (Universitas Lancang Kuning, 2023)
Diagnostic tests are strategies used in differentiated learning to adjust the course of learning based on students' existing learning needs. There are several types of diagnostic tests, including the three-tier diagnostic test. Explaining a three-tier diagnostic test instrument that is suitable for use in studying differentiated excretory systems is the aim of this research. The research method is research & development with 4D as a development model. 33 students of class The instrument developed consisted of 20 questions which were then tested for content and empirical validity. Based on the results of validity testing, an average of 92% was obtained, which shows that the instrument is very valid. Empirical validity testing obtained 13 valid questions and 7 invalid questions. In addition, a value of 0.732 was obtained from the reliability testing results, which shows that the instrument developed is reliable. Based on the results of testing the level of difficulty of the questions, it was found that there were 3 easy questions, 10 medium ones, and 7 difficult ones, and from the results of testing the differentiating power of the questions it was found that the questions were not good because they had a negative value of 1, bad had 3, fair and good each had 7, respectively. and very well collected 2. Based on content and empirical validity testing, the results showed that only 13 questions could be used in the differentiated excretion learning system, while the other 7 questions could not be used.